Tax Literacy Rate Among Taxpayers: Evidence from Malaysia - Ahmed Razman Abdul Latiff; Bany Ariffin Amin Noordin; Mohamad Raflis Che Omar; Dwipraptono Agus Harjito (Jurnal Akuntansi dan Auditing Indonesia, 2005)
The extent of taxpayer knowledge can have a major impact on the degree of compliance with taxation rules and regulation. Low knowledge creates uncertainty about requirements of the tax regulation and can lead to high degree of involun-tary non-compliance. This study high¬lighted the importance of taxation knowledge by measuring Malaysian’s tax payers’ tax literacy rate taking into consideration the following criteria: 1) Individual ability to fill the tax return form inde¬pendently, 2) Taxpayer’s interest in learning about tax, and 3) Incident of errors in filling the tax re¬turn forms. Questionnaires were used in this study to ascertain the tax liter-acy rate. The results in¬dicate that among the respondents, professionals group has the highest percentage of tax literacy and the formers have the lowest percentage. Majority of the businessmen paid for services for fill¬ing tax return forms and high rank officers are the highest among the group for not employing oth¬ers for filling the tax forms. Businessmen have the highest incidence of error in filling tax return form and most of teachers reported no error in filling such forms. Most business-men showed interests and were willing to spend time to learn about taxation. They perceived taxation knowledge as an important tool for themselves and also for their family. Overall results indicate that more than 60% of respondents are tax lit-erate. However, a significant number of them are actually‘ functionally tax illiter-ate’. Most of them thought that they knew a lot about taxation as they had read them in the tax literature sent to them by the IRB. However, the evidence was con-trary to this conjecture. The in¬formation on the extent of taxpayers’ knowledge is potentially useful to the tax authorities to assist them in developing effective com-pliance enhancement policiesKeywords: tax literacy rate, tax return